Toxicity of Decolorized Batik Wastewater on Common Carp Using Combination of Chitosan and Spent Mushroom Substrate - Swastika Oktavia; Nisa Haerunissa; Cory Novi (Poltekkes Kemenkes Surabaya, 2025)
Decolorization is a key treatment process in batik industry wastewater management, aimed at reducing color intensity. This study evaluates a decolorizing combination of chitosan from Litopennaeus vannamei (CLV) and spent mushroom substrate from Pleurotus ostreatus (SMSPO), examining its effect on the 96-hour LC50 value and scale structure of common carp. Using a completely randomized design, common carp was exposed to decolorized wastewater at concentrations of 0%, 1.875%, 3.75%, 7.5%, 15%, and 30%. Results show that decolorized wastewater at 7.5% concentration remains lethal to fish, while concentrations of 3.75% and below are non-lethal. Microscopic changes in fish scales indicate particle adhesion from the wastewater. The 96-hour LC50 for untreated wastewater is 5.663%, compared to 4.788% after decolorization, reflecting a slight decrease in toxicity. These findings suggest that C-LV and SMS-PO combination could contribute to sustainable wastewater treatment practices by reducing toxicity in batik industry effluent.